Extraction Of Collagen From Fish Orientai Sole Brachirus orientalis Skin And Studying Of Some Chemical Charactristics And Amino Acid Composition - AL-Mossawi, Aum-El-Basher, H.J.; Eskander, Mohammed Zyarah (Iraqi Journal of Aquaculture, 2021)
This study includes the extraction of acid soluble collagen (Acetic acid 0.5 M) from fish Oriental sole skin . After the removal of fat and non-collagenous proteins and dialyzed against distilled water, some the chemical properties were studied, that includes chemical composition and the percentage of yield were 12.15 % on the basis of wet weight. According to the electrophoretic patterns, the collagen consisted of two different chains (α1 and α 2), were characterized to be type I, β chain components as well as the observed was larger molecular weight , When estimating amino acid collagen observed that there is variation in the percentage of amino acid major such as glycine , proline , hydroxyproline and hydroxy lysine, When measuring the absorption spectrum of ultraviolet (UV) there was a single peak absorption at 232 nm for collagen fish skin, FTIR showed regions of amides A, B, I, II and III were 3408.57, 2934.89, 1651.73, 1540.85 and 1243.38 cm-1 respectively.